Selective Synthesis of Biogasoline Precursor from Renewable Platform Molecules at Ambient Temperature. (May 2017) - Long, Jinxing; Zhang, Xiong; Lv, Cheng; Liu, Sijie; Song, Changhua; Li, Xuehui
Abstract: The condensation of the dilute platform biochemical from the renewable lignocellulosic cellulose depolymerization for high quality energy production has attracted increasing attention currently. In this study, we propose an efficient process for biogasoline precursor production from the furfural and ethyl levulinate through the Aldol reaction at the ambient temperature. The results show that the furfural and ethyl levulinate can be efficiently condensed with the catalyst of commercial alkalis. Under the optimized condition, 78% of the product isolated yield can be obtained in the presence of KOH. Furthermore, the final product analysis using FT-IR, GPC, 1 H-NMR, 13 C-NMR and elemental analysis demonstrates that it mainly composes of 3-(furan-2-yl(hydroxy)methyl)-4-oxopentanoate acid, an excellent precursor for C9 branched hydrocarbon of gasoline. Moreover, the investigation shows that the product distribution of this Aldol process is high temperature dependent, higher temperature resulting in the recondensation of the product, hence decreasing the C9 gasoline precursor selectivity.